Limobrevibacterium gyesilva gen. nov., sp. nov., Isolated from Forest Soil - Nhan Le Thi Tuyet; Jaisoo Kim (Diversity, 2023)
An aerobic, oxidase-positive, catalase-negative, non-motile, oval/rod-shaped, and Gram-negative strain RN2-1T was isolated from a Korean forest soil sample. Cells grew in a pH range of 6–9 (optimum range: 7–8), in a temperature range of 20–40 °C (optimum range: 30–35 °C), and in the presence of 0–1% (w/v) NaCl. The major polar lipid profile consisted of phosphatidylglycerol, diphosphatidyl glycerol, phosphatidylethanolamine, phosphatidylcholine, and a group of phospholipids, aminolipids, and polar lipids with unidentified structures. The major quinone was ubiquinone 10. The main fatty acids were summed feature 8 (C18:1 ω7c/C18:1 ω6c), C16:0, Cyclo-C17:0, cyclo C19:0 ω8c, and C18:1 2OH. Phylogenetic similarities based on 16S rDNA sequences showed that strain RN2-1T grouped in the family Acetobacteraceae included the genera Rhodovastum, Acidisoma, Acidisphaera, and Acidibrevibacterium. The aerobic phototrophic bacterium Rhodovastum atsumiense G2-11T was the closest relative to RN2-1T (96.04% sequence similarity). Genomic DNA revealed 68.7% G+C content. Whole genome analysis and phenotypic data of the strain RN2-1T confirmed its distinctive phylogenetic location within the family Acetobacteraceae. Because of these results, strain RN2-1T represents the novel species of a new genus for which the name Limobrevibacterium gyesilva gen. nov., sp. nov. was proposed. The type of strain was strain RN2-1T (KACC 23001 = JCM 35944).